MCSE/MCSA Implementing a Window Server 2003 Network Infrastucture : - McCaw, Rory (McGraw-Hill, 2004)
The only classroom-based integrated study system for professional certification has been fully redesigned throughout--find out not only what to study, but "how to study. You'll get 100% complete coverage of all objectives for exam 70-291, hundreds of practice exam questions, and hands-on exercises. The CD-ROM features full practice exam software with interactive tutorials and lab simulations, plus an adaptive test engine